2016
DOI: 10.1589/jpts.28.2727
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of home-based exercise programs for low back pain patients

Abstract: [Purpose] The purpose of this study was to investigate the effectiveness of home-based exercise programs for low back pain (LBP) patients. [Subjects and Methods] The study subjects were 49 volunteer chronic LBP patients. Home-based exercises that had been specifically modified for the individual patients were prescribed for a period of four weeks, and the volunteers were asked to return for a control evaluation at the end of this period. Exercise adherence and correct performance, pain intensity, disability, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The results of this systematic review support supervised exercise programs in preference to unsupervised exercise programs completed in the home setting. While unsupervised exercise programs in the home setting are beneficial in that they are low cost, accessible, safe and easy to implement [ 46 ], adherence may potentially be an issue and is influenced by multiple factors such as age, motivation, believing in its benefits, follow ups and the complexity of exercises prescribed [ 47 ]. Two studies [ 43 , 44 ] measured self-reported adherence to non-weight bearing exercise in the home setting in the form of an exercise log, where participants were required to record the type and number of exercises completed.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this systematic review support supervised exercise programs in preference to unsupervised exercise programs completed in the home setting. While unsupervised exercise programs in the home setting are beneficial in that they are low cost, accessible, safe and easy to implement [ 46 ], adherence may potentially be an issue and is influenced by multiple factors such as age, motivation, believing in its benefits, follow ups and the complexity of exercises prescribed [ 47 ]. Two studies [ 43 , 44 ] measured self-reported adherence to non-weight bearing exercise in the home setting in the form of an exercise log, where participants were required to record the type and number of exercises completed.…”
Section: Discussionmentioning
confidence: 99%
“…This programme comprises different exercises adapted for each patient, which should be carried out independently during rehabilitation and thereafter at home for at least 3 months. The effectiveness of this specific type of training has been described and proved in many studies [2][3][4][5][6][7]. O'Reilly et al [8] conclude that a simple home-based exercise programme to strengthen the quadriceps muscles for patients with osteoarthritis of the knee could significantly improve knee pain and function.…”
Section: Introductionmentioning
confidence: 98%
“…4,5 Low back pain classified as chronic when symptoms persist for more than 12 weeks. 6 Currently available self-management options for chronic non-specific low back pain need considerable improvements. 7 Educating the patients, proper ergonomics and postures and proper body lifting were found to be effective in reducing chronic low back pain and disability and improving quality of life alongside general strengthening and stretching exercises.…”
Section: Introductionmentioning
confidence: 99%
“…8 Home exercise programme showed to be effective in treatment of chronic low back pain, but there was low adherence to and improper application of exercises. 6,9 All of these are available in numerous smartphone applications educating patients for self-management of low back pain. However, these applications were not developed by professionals, not based on scientific evidence, and/or their effectiveness was not established.…”
Section: Introductionmentioning
confidence: 99%